Risk eller frisk? Tvärprofessionell samverkan för att förebygga att barn i förskola och skola hamnar i svårigheter - Maria Olsson (Dalarna university, 2024)
This article contributes knowledge regarding professionals' expectations and conceptions of what initiatives in pedagogical practice, multiprofessional cooperation for supporting children "at risk", can generate or has generated. The data derive from semi-structured interviews with professionals involved in a project in a Swedish municipality that aimed by means of improved multi-professional collaboration to prevent children from getting into difficulties. In this article, Billig's concept of ideological dilemmas was used as theoretical framework, and the data analysis was inspired by qualitative content analysis. The presented ideological dilemmas - rhetoric versus practice and the individual versus the collective - relate to contrasting overarching logics associated with education and social services: promoting all children's health and development versus treating individuals' potential deficiencies. This article suggests that discussions about the intentions of multiprofessional collaboration need to be held when opposing positions can be articulated. Such discussions, based on professionals' experiences and knowledge, may lead to the development of multiprofessional collaboration.